2015
DOI: 10.3390/v7082842
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Wnt/β-Catenin Signaling Pathway by Human Papillomavirus E6 and E7 Oncoproteins

Abstract: Cell signaling pathways are the mechanisms by which cells transduce external stimuli, which control the transcription of genes, to regulate diverse biological effects. In cancer, distinct signaling pathways, such as the Wnt/β-catenin pathway, have been implicated in the deregulation of critical molecular processes that affect cell proliferation and differentiation. For example, changes in β-catenin localization have been identified in Human Papillomavirus (HPV)-related cancers as the lesion progresses. Specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
81
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 135 publications
(132 reference statements)
0
81
1
Order By: Relevance
“…The E6 and E7 oncoproteins interfere with cell cycle regulators and induce genomic instability, which results in a malignant phenotype19. In addition to cervical cancer, E6/E7 is also associated with other tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The E6 and E7 oncoproteins interfere with cell cycle regulators and induce genomic instability, which results in a malignant phenotype19. In addition to cervical cancer, E6/E7 is also associated with other tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the Wnt/b-catenin pathway in the development of different types of skin neoplasm has not been fully elucidated yet. Previous research described a relocalization of b-catenin from the plasma membrane to the nucleus in the presence of the E6/E7 oncoproteins of the high-risk a-HPV type 16 (Bello et al, 2015), which is associated with cervical and oropharyngeal cancer (Hübbers & Akgül, 2015). Our results demonstrated that the levels of membrane-tethered b-catenin are elevated in HPV8-E7 positive cutaneous keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…29 Moreover, activating phosphorylations of NICD can be conducted by GSK3β which forms part of the Wnt degradation complex. 30 In contrast, Wnt can modulate Notch signaling activity through direct inhibition of RBP-Jĸ by the disheveled protein, which mediates β-catenin half-life. 31 The phosphatidylinositol-3-kinase (PI3K) pathway is a key regulator of cell survival; it transduces signals from growth factors and cytokines by generating phospholipids which activate Akt.…”
Section: Crosstalk Of Notch With Cancer Pathwaysmentioning
confidence: 99%
“…Wnt is known to affect the Notch signaling pathway by promoting JAG1 and NUMB expression . Moreover, activating phosphorylations of NICD can be conducted by GSK3β which forms part of the Wnt degradation complex . In contrast, Wnt can modulate Notch signaling activity through direct inhibition of RBP‐Jĸ by the disheveled protein, which mediates β‐catenin half‐life …”
Section: Introductionmentioning
confidence: 99%